2006
DOI: 10.1176/ajp.2006.163.10.1791
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cancer-Specific Thought Intrusions and Anxiety Symptoms With a Stress Management Intervention Among Women Undergoing Treatment for Breast Cancer

Abstract: Objective-After surgery for breast cancer, many women experience anxiety relating to the cancer that can adversely affect quality of life and emotional functioning during the year postsurgery. Symptoms such as intrusive thoughts may be ameliorated during this period with a structured, group-based cognitive behavior intervention.Method-A 10-week group cognitive behavior stress management intervention that included anxiety reduction (relaxation training), cognitive restructuring, and coping skills training was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 45 publications
6
132
0
3
Order By: Relevance
“…The data indicated that women who participated in this 16-week group therapy program benefited, showing reduced anxiety, depression, and distress. Previous studies demonstrated that a groupbased stress management intervention can significantly decrease cancer-specific intrusive thoughts, general anxiety symptoms and overall negative mood in women who are moving through their medical treatment for cancer (Sheard et al, 1999;Montazeri et al, 2001;Montgomery 2002;Antoni et al, 2006;Reutera et al, 2010, Loprinzi et al, 2011. Loprinzi et al found similar results with that of our study.…”
Section: Discussionsupporting
confidence: 90%
“…The data indicated that women who participated in this 16-week group therapy program benefited, showing reduced anxiety, depression, and distress. Previous studies demonstrated that a groupbased stress management intervention can significantly decrease cancer-specific intrusive thoughts, general anxiety symptoms and overall negative mood in women who are moving through their medical treatment for cancer (Sheard et al, 1999;Montazeri et al, 2001;Montgomery 2002;Antoni et al, 2006;Reutera et al, 2010, Loprinzi et al, 2011. Loprinzi et al found similar results with that of our study.…”
Section: Discussionsupporting
confidence: 90%
“…standardized bed and wake-up times, avoidance of daytime napping, and correction of maladaptive beliefs about sleep). [116][117][118][119][120][121][122][123][124][125][126][127] Such interventions may limit the impact of stress on the immune response and may have direct effects on neuroendocrine-immune interactions. Indeed, psychological interventions such as cognitive-behavioral stress management and mindfulness-based stress reduction have been shown to alleviate psychological distress in breast cancer patients, while increasing lymphocyte proliferative responses and normalizing diurnal cortisol secretion.…”
Section: Therapeutic Ramificationsmentioning
confidence: 99%
“…Additionally, in the last few decades, many researches were focused on stress response after cancer-diagnosis and during treatment while no further recent data were added on stress induced disease. There is no doubt about the role of positive psychological support: although it is widely accepted that the psychological support for cancer patients (by family), is both the most helpful in managing distress and may also be the most harmful if mismanaged [13][14][15].…”
Section: Data On Stress Induced Disease: From History To Nowadaysmentioning
confidence: 99%